Seroepidemiological study of Q fever in domestic ruminants in semi-extensive grazing systems - Ruiz-Fons, Francisco (BioMed Central, 2010)
BACKGROUND: Q fever, a worldwide zoonotic disease caused by Coxiella burnetii, is endemic in northern Spain where it has been reported as responsible for large series of human pneumonia cases and domestic ruminants' reproductive disorders. To investigate pathogen exposure among domestic ruminants in semi-extensive grazing systems in northern Spain, a serosurvey was carried out in 1,379 sheep (42 flocks), 626 beef cattle (46 herds) and 115 goats (11 herds). Serum antibodies were analysed by ELISA and positive samples were retested by Complement Fixation test (CFT) to detect recent infections. RESULTS: ELISA anti-C. burnetii antibody prevalence was slightly higher in sheep (11.8 ± 2.0%) than in goats (8.7 ± 5.9%) and beef cattle (6.7 ± 2.0%). Herd prevalence was 74% for ovine, 45% for goat and 43% for bovine. Twenty-one percent of sheep flocks, 27% of goat and 14% of cattle herds had a C. burnetii seroprevalence ≥ 20%. Only 15 out of 214 ELISA-positive animals reacted positive by CFT. Age-associated seroprevalence differed between ruminant species with a general increasing pattern with age. No evidence of correlation between abortion history and seroprevalence rates was observed despite the known abortifacient nature of C. burnetii in domestic ruminants. CONCLUSIONS: Results reported herein showed that sheep had the highest contact rate with C. burnetii in the region but also that cattle and goats should not be neglected as part of the domestic cycle of C. burnetii. This work reports basic epidemiologic patterns of C. burnetii in semi-extensive grazed domestic ruminants which, together with the relevant role of C. burnetii as a zoonotic and abortifacient agent, makes these results to concern both Public and Animal Health Authorities.